2018
DOI: 10.1093/jnen/nly031
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Clinical Risk Factors and Histological Features in Ruptured and Unruptured Human Intracranial Aneurysms: The Swiss AneuX Study

Abstract: Pathogenesis of intracranial aneurysm is complex and the precise biomechanical processes leading to their rupture are uncertain. The goal of our study was to characterize the aneurysmal wall histologically and to correlate histological characteristics with clinical and radiological factors used to estimate the risk of rupture. A new biobank of aneurysm domes resected at the Geneva University Hospitals (Switzerland) was used. Histological analysis revealed that unruptured aneurysms have a higher smooth muscle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 32 publications
2
63
2
Order By: Relevance
“…The first histological alteration of cerebral arteries leading to IA formation is the destruction of the IEL . Although the histological evolution between a healthy cerebral artery to the different steps of IA growth and rupture is not completely known, several studies have shown that the lack of IEL is associated with erosion of luminal endothelium, infiltration of inflammatory cells, loss of SMCs, destruction of the extracellular matrix (ECM), activation of the innate immunity, calcification and/or lipid accumulation . Frösen et al have classified the IA wall in 4 groups using the following parameters: (a) endothelialized wall with linearly organized SMCs; (b) thickened wall with disorganized SMCs; (c) hypocellular wall with either intimal hyperplasia or organizing luminal thrombosis; (d) an extremely thin thrombosis‐lined hypocellular wall.…”
Section: Pathogenesis Of Iasmentioning
confidence: 99%
See 2 more Smart Citations
“…The first histological alteration of cerebral arteries leading to IA formation is the destruction of the IEL . Although the histological evolution between a healthy cerebral artery to the different steps of IA growth and rupture is not completely known, several studies have shown that the lack of IEL is associated with erosion of luminal endothelium, infiltration of inflammatory cells, loss of SMCs, destruction of the extracellular matrix (ECM), activation of the innate immunity, calcification and/or lipid accumulation . Frösen et al have classified the IA wall in 4 groups using the following parameters: (a) endothelialized wall with linearly organized SMCs; (b) thickened wall with disorganized SMCs; (c) hypocellular wall with either intimal hyperplasia or organizing luminal thrombosis; (d) an extremely thin thrombosis‐lined hypocellular wall.…”
Section: Pathogenesis Of Iasmentioning
confidence: 99%
“…Frösen et al have classified the IA wall in 4 groups using the following parameters: (a) endothelialized wall with linearly organized SMCs; (b) thickened wall with disorganized SMCs; (c) hypocellular wall with either intimal hyperplasia or organizing luminal thrombosis; (d) an extremely thin thrombosis‐lined hypocellular wall. Based on this classification, it has been shown in Finnish and Swiss cohorts of patients affected by IA that ruptured aneurysmal domes are in vast majority histologically characterized by hypocellular and/or very thin vascular walls and luminal thrombosis (grades c and d). In contrast, unruptured IAs contain ECs and/or a thickened media with SMCs (grades a and b).…”
Section: Pathogenesis Of Iasmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebral aneurysms (CA) occur in 20-50 people per 1000 of population and depend a little on race and age [1,2] while correlation with gender remains a controversial subject. One of the main challenges in modern neurosurgery is determining the stage of aneurysm for the subsequent estimating of the risks of its rupture.…”
Section: Introductionmentioning
confidence: 99%
“…3). The infrastructure so far allows for collecting data and managing biological samples to contribute in particular to the identification of genetic loci associated with the disease, 19,20 assessing the aneurysm growth rate in the cohort of followed-up patients, 10 assessing the predictive performance of an aneurysm rupture risk classifier based on location and size, 2 PHASES score 3 and cerebrovascular morphodynamic factors, 6 and correlating clinical risk factors with histological characteristics of disease severity 5,16 and associating biomechanical stress conditions with aneurysm initiation and growth. 9,14 Analysis of the impact of different phenotypic and genetic factors on aneurysm initiation, multiplicity, and rupture is ongoing.…”
Section: Database Design and Disease Modelingmentioning
confidence: 99%